2022
DOI: 10.3389/fcell.2022.1019715
|View full text |Cite
|
Sign up to set email alerts
|

The different clinical facets of SYN1-related neurodevelopmental disorders

Abstract: Synapsin-I (SYN1) is a presynaptic phosphoprotein crucial for synaptogenesis and synaptic plasticity. Pathogenic SYN1 variants are associated with variable X-linked neurodevelopmental disorders mainly affecting males. In this study, we expand on the clinical and molecular spectrum of the SYN1-related neurodevelopmental disorders by describing 31 novel individuals harboring 22 different SYN1 variants. We analyzed newly identified as well as previously reported individuals in order to define the frequency of key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…It is primarily expressed in the central and peripheral nervous systems and is associated with early neuronal development, synaptic growth and development, and regulation of neurotransmitter release. Changes in Syn1 lead to alterations in synaptic homeostasis, which have been shown to cause neuronal developmental disorders, and the regulation of Syn1 expression has been shown to promote neuronal dendrite growth (Yan, et al 2022;Hedegaard, et al 2013;Parenti, et al 2022). The results of this study showed that as the exposure concentration increased, the protein expression levels of BDNF and Syn1 in the hippocampal tissue of SD rats were significantly reduced.…”
Section: Discussionmentioning
confidence: 59%
“…It is primarily expressed in the central and peripheral nervous systems and is associated with early neuronal development, synaptic growth and development, and regulation of neurotransmitter release. Changes in Syn1 lead to alterations in synaptic homeostasis, which have been shown to cause neuronal developmental disorders, and the regulation of Syn1 expression has been shown to promote neuronal dendrite growth (Yan, et al 2022;Hedegaard, et al 2013;Parenti, et al 2022). The results of this study showed that as the exposure concentration increased, the protein expression levels of BDNF and Syn1 in the hippocampal tissue of SD rats were significantly reduced.…”
Section: Discussionmentioning
confidence: 59%
“… 49 Synapsins (Syn1, Syn2) are a family of presynaptic phosphoproteins with roles in neuronal development through the regulation of the number of synaptic vesicles available for neurotransmitter release. 50 The Arp2/3 complex regulates the actin-myosin network and is subsequently involved in dendrite development and function. 51 , 52 …”
Section: Resultsmentioning
confidence: 99%
“…Due to their involvement in synaptogenesis and neurotransmitter release control, synapsins may play a crucial role in various neuropsychiatric disorders. (5) Previous studies have reported low expression of SYN1 in several medulloblastoma cell lines. (6)…”
Section: Introductionmentioning
confidence: 99%